Answer:
this is my answer but it's on you if you think this answer is correct or wrong
Answer:
4
Step-by-step explanation:
Based on the information you have given me, p = 1/3.
All we need to do is substitute that value into the expression:
12p = 12(1/3) = 4
Answer:
Step-by-step explanation:
Answer:
(X-3)^2 - 4
Step-by-step explanation:
Answer:
Step-by-step explanation:
Recall these rules of logs: log a + log b = log (ab), and log a^b = b log a
Then 3 log q = log q^3 and 6 log v = log v^6, and
log q^3 + 6 log v becomes log q^3 * v^6
Now rewrite this using b as the base:
log q^3 * v^6
b